"The Swedish model" expression in the French press in 2022 - Premat, Christophe (Stockholm University, 2024)
These are data from two corpora studied for an article that will be published in the journal Sur le journalisme with the title: Splendeurs et misères de l’expression « modèle suédois » : étude de la formule dans la presse française en 2022. The first file compiles articles from the year 2022 obtained through the Nexis Uni software. The second document is a visualization of data from the Timestamped JSI web corpus 2014-2021 French processed by the SketchEngine software.
Keywords: Discourse and pragmatics; Languages and Literature; Språk och litteratur